The Relationship between Functional Groups and Gaseous Productions and Micropore Structures Development of Coal Oxidized at Low Temperature under Methane-Diluted Atmospheres. Issue 8 (3rd August 2019) - Cai, Jiawen; Yang, Shengqiang; Hu, Xincheng; Xu, Qin; Zhou, Buzhuang; Zhang, Zhicheng
ABSTRACT: As coal reservoirs containing high methane content are more prone to spontaneous combustion, disasters caused by the combined effects of methane and coal spontaneous combustion have been increasingly prominent. Given that air flows in different zones in a goaf contain methane with different contents, the mechanism governing the changes of micropores and functional groups of left-over coal subjected to spontaneous combustion in a goaf with air flows containing methane were investigated by sufficiently considering the diluted influence of methane. The change of microscopic functional groups and variation of gaseous products from coal oxidized at low-temperature (i.e., 70°C< it < 230°C) under different oxidizing atmospheres were separately acquired by employing Fourier transform infrared spectroscopy (FTIR) and gas chromatography. By using the Brunauer, Emmett and Teller (BET) method, a low-temperature nitrogen adsorption experiment was carried out on coal samples taken from the Shigang coal mine in Shanxi province, China under different methane-diluted oxidizing atmospheres. The results showed that the content of aliphatic hydrocarbons (methyl and methylene) of the coal oxidized at low temperature decreased with rising oxidizing temperature and reached a maximum at the condition of a 25% methane concentration. Meanwhile, other oxygen-containing functional groups and corresponding gaseous products were generated. The aforementioned results indicated that the initial temperature for the generation of CO and the amount generated both showed delayed effects in oxidizing atmospheres with different methane concentrations. By carrying out a low-temperature nitrogen adsorption experiment, it was determined that the average sizes of the pores in coal decreased in an oxidizing atmosphere (i.e., < 15% methane concentrations at a high temperature). However, the specific surface area (SSA) and accumulative total internal surface area of the pores increased. Additionally, the pore structure in the coal tended to be microscopic and complex in the aforementioned oxidizing atmosphere, as determined by using the fractal dimension D. The pore structure in the coal was increasingly complex after being oxidized in an oxidizing atmosphere containing methane, which increased the likelihood of the coal oxidation reaction and increased the occurrence probability of coal spontaneous combustion.